Experimental Assessment of a Modular Multilevel Converter Using Opal-Rt Control and Power Stages - Diaz-Diaz, M; Rojas-Aceituno, A; Ibaceta-Valenzuela, E (Institute of Electrical and Electronics Engineers Inc., 2022)
Modular Multilevel Converters are being widely used in high-power applications such as High-Voltage Direct Current transmission due to the main advantages of scalability, modular configuration and high-quality power. For industrial applications, hundreds of power cells have to be connected in a cascade to reach high-power ratios. However, most of the current academic research is validated using prototypes equipped with a low number of power cells. Consequently, this paper presents the testing and start-up procedure of 60 power cells Modular Multilevel Converter test-bench based on an OPAL-RT real-time controller and power stage. Partial experimental results are presented. © 2022 IEEE.